PHIPS-HALO: the airborne particle habit imaging and polar scattering probe - Part 2: Characterization and first results - Schnaiter, Martin; Abdelmonem, Ahmed; Leisner, Thomas (Atmospheric measurement techniques, 2018)
The novel aircraft optical cloud probe PHIPS-HALO has been developed to establish clarity regarding the fundamental link between the microphysical properties of single atmospheric ice particles and their appropriated angular light scattering function. After final improvements were implemented in the polar nephelometer part and the acquisition software of PHIPS-HALO, the instrument was comprehensively characterized in the laboratory and was deployed in two aircraft missions targeting cirrus and Arctic mixed-phase clouds. This work demonstrates the proper function of the instrument under aircraft conditions and highlights the uniqueness, quality, and limitations of the data that can be expected from PHIPS-HALO in cloud-related aircraft missions.
Gesehen am 16.02.2018